2022
DOI: 10.1038/s42003-022-03741-x
|View full text |Cite
|
Sign up to set email alerts
|

Alpine shrub growth follows bimodal seasonal patterns across biomes – unexpected environmental controls

Abstract: Under climate change, cold-adapted alpine ecosystems are turning into hotspots of warming. However, the complexity of driving forces of growth, associated biomass gain and carbon storage of alpine shrubs is poorly understood. We monitored alpine growth mechanisms of six common shrub species across contrasting biomes, Mediterranean and tundra, using 257 dendrometers, recording stem diameter variability at high temporal resolution. Linking shrub growth to on-site environmental conditions, we modelled intra-annua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 70 publications
(141 reference statements)
1
14
0
Order By: Relevance
“…The observed bimodality in cambial activity can be interpreted as a response to the separation of favorable conditions before and after summer drought (de Luis et al 2007, Camarero et al 2010. It has also been suggested to be present in Mediterranean alpine perennial forbs (Olano et al 2013) and was previously observed in the Mediterranean alpine shrubs studied here (Dobbert et al 2022a).…”
Section: Introductionsupporting
confidence: 74%
See 3 more Smart Citations
“…The observed bimodality in cambial activity can be interpreted as a response to the separation of favorable conditions before and after summer drought (de Luis et al 2007, Camarero et al 2010. It has also been suggested to be present in Mediterranean alpine perennial forbs (Olano et al 2013) and was previously observed in the Mediterranean alpine shrubs studied here (Dobbert et al 2022a).…”
Section: Introductionsupporting
confidence: 74%
“…As such, resource acquisition is rather optimized during phases when the traits and growth strategies of the species allow for physiological activity at high gain and low costs, resulting in species-specific windows of maximum growth (and heterotrophic growth in A. granatensis). This is of major importance for understanding the adaptive capacity in alpine environments under future climate variability (Olano et al 2013, Kramp et al 2022, Dobbert et al 2022a and contributes to the question of when and how woody plants grow (Jevšenak et al 2022), the knowledge of which is crucial for assessing vegetation evolution across biomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under the ongoing Arctic and low-Arctic warming trends and future projections (IPCC, 2021), tundra shrub will also likely become less temperature-limited and more moisture limited, especially if the warming is coupled with insufficient water availability (Weijers, 2022;Weijers et al, 2017). Recent investigations performed through direct growth measurements with dendrometers, highlighting a bimodal response to climate (Dobbert, Albrecht, et al, 2022;, or adopting satellite-derived vegetation indices (Myers-Smith et al, 2020;Phoenix & Bjerke, 2016), seem to confirm this scenario. However, our results suggest that Icelandic long-lived woody species are currently experiencing a pervasive boost in secondary growth, with tundra shrub rapidly growing and most likely expanding its distribution.…”
Section: Contrary To Our Hypotheses and As Previously Highlighted Bymentioning
confidence: 99%